NO-sensing performance of vacancy defective monolayer MoS2 predicted by density function theory - Li, Feifei; Shi, Changmin (Applied surface science, 2018)
[Display omitted] •The interaction between NO molecule and pure MoS2-ML is weak.•The pure MoS2-MLs act as donors, which lead to p-type conductivity behavior.•MoS3 and S-vacancy defective MoS2-MLs show stronger chemisorption and greater electron transfer effects than pure MoS2-ML.•The order of electron transfer is: S-vacancy>MoS3-vacancy>pure. Using density functional theory (DFT), we predict the NO-sensing performance of monolayer MoS2 (MoS2-MLs) with and without MoS3-vacancy/S-vacancy defects. Our theoretical results demonstrate that MoS3- and S-vacancy defective MoS2-MLs show stronger chemisorption and greater electron transfer effects than pure MoS2-MLs. The charge transfer analysis showed pure and defective MoS2-MLs all act as donors. Both MoS3-vacancy and S-vacancy defects induce dramatic changes of electronic properties of MoS2-MLs, which have direct relationship with gas sensing performance. In addition, S-vacancy defect leads to more electrons transfer to NO molecule than MoS3-vacancy defect. The H2O molecule urges more electrons transfer from MoS3- or S-vacancy defective MoS2-MLs to NO molecule. We believe that this calculation results will provide some information for future experiment.